Shame and Honor in the Book of Esther - Crawford, Sidnie White (Journal of Semitic studies, 2002)
Shame and Honor in the Book of Esther Timothy S.Laniak (SBL Dissertation Series 165). Scholars PressAtlanta 1998xiii + 205Hardback$34.95 0‐7885‐0505‐X , 1University of Nebraska‐Lincoln